STUDI KOMPARATIF EUTHANASIA AKTIF SEBAGAI BENTUK EKSEKUSI BAGI TERPIDANA MATI YANG LEBIH MANUSIAWI DAN BERADAB - I Komang Mahardika Wijaya (Jurnal Komunikasi Hukum, 2023)
This research is a normative research (legal research) using the method of collecting library studies. This research topic is divided into two issues. The first topic is how to regulate the execution of executions in Indonesia and the second topic is whether the implementation of active euthanasia as a more humane and civilized form of execution.The Constitutional Court affirmed the inclusion of the death penalty both in the Criminal Code and outside the Criminal Code with Decision Number 21/PUU-VI/2008 which stated that the imposition of the death penalty did not contradict the Constitution. According to Article 99 (3) of the new Penal Code, "the death penalty shall be carried out by shooting prisoners by firing squad or by any other means prescribed by law."Carrying out the death penalty according to the regulated law is still an inhumane and uncivilized thing, therefore the author came up with the idea to introduce active euthanasia as a form of execution of the death penalty in Indonesia.The definition of euthanasia which is none other than ending life in an easy and painless way or commonly called mercy killing (death peacefully). The discussion was accompanied by a comparative study of executions in California, which involves injecting substances into a vein in lethal amounts sufficient to cause death, as instructed by the Department of Corrections and Rehabilitation.